Design and analysis of the test section for an open channel flow flume - Sazwan, Sahar (2013)
The needs of renewable energy is now in urgency as the source of the fossil energy is depleting from day to day. This study will focus on the potential energy extraction from the river flow to generate electricity and aiming is to design and analyze the test section for an open channel flume. The objective of the study is to design and analyze the test section for an open channel flume. Five concept designs for a flume were constructed and Flow Simulation Package was used to simulate the flow condition in the developed models. Result indicated that there is a significant difference across the test section between all the five designs in terms of pressure drop, velocity, turbulence intensity, as well as the velocity profile pattern. Based on the investigation, the best result derived from Design 5 which has been resulted in the average velocity of 3.36 m/s in the test section, average total pressure of 1172.5 kPa with the pressure drop of 6.56 kPa, and average turbulence intensity of 21.15%. Velocity profile gave a normal pattern and in agreement with the principal of zero-slip condition. These finding led to the conclusion that Design 5 configuration gave the best quality of flow condition and properties in the test section compared to the other four designs based on the analysis result.